Corrective feedback on essay writing: English as second language teachers’ and students’ perspectives - Yaseen, Muhammad; Hamzah, Mohd Hilmi; Harun, Minah (International Journal of Evaluation and Research in Education (IJERE), 2024)
Many studies have examined how written corrective feedback (WCF) can raise English as a foreign language (EFL) students’ understanding of language concepts. However, not much is known about how students’ perceptions and preferences could influence the effects of WCF. This study examined how Secondary School Certificate (SSC) students and teachers in Pakistan International School, Saudi Arabia, felt about WCF in writing classes. It aimed to identify the WCF aspects of the target language the students preferred. A questionnaire survey was distributed to 30 SSC-level EFL students and 10 teachers at the school who participated voluntarily in the study. The findings revealed that the students had sympathetic perspectives despite having preferences for WCF. They mainly believed that WCF might help them enhance their language knowledge and writing abilities. Through WCF, they learned what to avoid and how to write better. The teachers also found WCF helpful in enhancing the basic understanding of the target language. The findings showed that the students and teachers believed direct WCF to be the most effective technique for improving the former’s writing abilities, followed by indirect strategies such as underlining errors or providing codes. The research was considered relevant and pertinent as it addressed diverse aspects of WCF.